Timing of Return to Dialysis in Patients with Failing Kidney Transplants. Issue 6 (9th September 2013) - Molnar, Miklos Z.; Ichii, Hirohito; Lineen, James; Foster, Clarence E.; Mathe, Zoltan; Schiff, Jeffrey; Kim, S. Joseph; Pahl, Madeleine V.; Amin, Alpesh N.; Kalantar‐Zadeh, Kamyar; Kovesdy, Csaba P.
Abstract In the last decade, the number of patients starting dialysis after a failed kidney transplant has increased substantially. These patients appear to be different from their transplant‐naïve counterparts, and so may be the timing of dialysis therapy initiation. An increasing number of studies suggest that in transplant‐naïve patients, later dialysis initiation is associated with better outcomes. Very few data are available on timing of dialysis reinitiation in failed transplant recipients, and they suggest that an earlier return to dialysis therapy tended to be associated with worse survival, especially among healthier and younger patients and women. Failed transplant patients may also have unique issues such as continuation of immunosuppression versus withdrawal or the need for remnant allograft nephrectomy with regard to dialysis reinitiation. These patients may have a different predialysis preparation work‐up, worse blood pressure control, higher or lower serum phosphorus levels, lower serum bicarbonate concentration, and worse anemia management. The choice of dialysis modality may also represent an important question for these patients, even though there appears to be no difference in mortality between patients starting peritoneal versus hemodialysis. Finally, failed transplant patients returning to dialysis appear to have a higher mortality rate compared with transplant‐naïve incident dialysis patients, especially in the first several months of dialysis therapy. In this review, we will summarize the available data related to the timing of dialysis initiation and outcomes in failed kidney transplant patients after returning to dialysis.